Workability and Compressive Strength of Seawater-Mixed Concrete Containing Rice Husk Ash as Supplementary Cementitious Material - Hussain, Zahid; Md Noor, Nurazuwa; Caronge, Muhammad Akbar (International Journal of Integrated Engineering, 2019)
The world is grappling with the challenge of rapidly growing water crises. The increasing population demands increased infrastructure which at present leads to the consumption of trillion gallons of water every year in construction industry. This research aims to check the suitability of seawater as an alternate to freshwater for mixing and curing of concrete. Rice husk ash is used as supplementary cementing material in order to enhance the capacity of matrix to sustain higher stress. Specimens were prepared with rice husk ash using fresh water and seawater. Half of the specimens were cured in seawater and remaining half with freshwater. The water-cement ratio in this study was kept constant equal to 0.39. Workability of concrete was determined for both fresh water and sea water mixes. Density and strength parameters were determined at the end of curing periods. The workability of concrete was found to decrease in seawater compared to freshwater mixes. With the addition of RHA it was found to decrease in both freshwater as well as in seawater. The density showed a declining path with the use of seawater and increasing amount of RHA. The specimens for determining compressive strength were tested at 7 and 28 days. The compressive strength results concluded that initially rate of gaining strength of seawater specimen was higher than its freshwater counterpart. The seawater specimen showed higher strength at 10% replacement of cement with rice husk ash at the end curing period. It can be concluded that seawater added with RHA is suitable alternative to fresh water in concrete.